2019
DOI: 10.3390/jmse7090285
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glacier Recession on Benthic and Pelagic Communities: Case Study in Herve Cove, Antarctica

Abstract: Changes in macrobenthic and pelagic communities in the postglacial, partially isolated, lagoon Herve Cove in Admiralty Bay, King George Island, were investigated 15 years after the first comprehensive studies had been conducted in this region. The bottom area of the cove has enlarged from approximately 12 ha to 19 ha after the retreat of the Dera Icefall. Based on a photographic survey of the benthos and taxonomic composition of zooplankton, ecological succession and the colonization of new species have been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…During the last few decades, the Antarctic ecosystem has been changing, mainly due to climatic fluctuations and the direct impacts of human activity [20,21]. These changes are visible not only in fluctuations of abiotic factors [22,23], but also at the functional level of the pelagic communities [24][25][26][27][28]. The responses of zooplankton to the warming Antarctic marine environment are very difficult to characterize due to the complex interactions between predators and prey [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades, the Antarctic ecosystem has been changing, mainly due to climatic fluctuations and the direct impacts of human activity [20,21]. These changes are visible not only in fluctuations of abiotic factors [22,23], but also at the functional level of the pelagic communities [24][25][26][27][28]. The responses of zooplankton to the warming Antarctic marine environment are very difficult to characterize due to the complex interactions between predators and prey [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, these animals are still very poorly studied, especially in polar regions, which is often due to the use of inadequate plankton nets, as well as difficulties in taxonomic identification [16,61]. Considering the above facts, the results of the research presented in this paper may offer a significant contribution to a better understanding of this group of animals in polar fjord environments, where the effects of ongoing climate change are most clearly and readily visible [28,35,62].…”
Section: Discussionmentioning
confidence: 97%
“…In Antarctic or sub-Antarctic bays or fjords, studies on larvaceans are even rarer. Fuentes et al [26] recorded Fritillaria borealis and Oikopleura gaussica in Potter Cove (King George Island), while Freire et al [27] found F. borealis in Admiralty Bay (King George Island), and Potocka et al [28] noted Appendicularia in Herve Cove (Admiralty Bay).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pelagic ecosystem consists of all the organisms that inhabit the middle waters of the oceans and seas. The species in this area are fish, phytoplankton, zooplankton, and predators [48][49][50]. The disposal of tailings in the sea has a more significant impact on the benthic fauna because they directly contact the seabed.…”
Section: Faunamentioning
confidence: 99%